Implementasi of technology acceptance model (TAM) in electronic documentation of nursing care: phenomenology explorative - Santoso, Erny Kristiana; Dedi, Blacius; Nurhayati, Susi (JHeS (Journal of Health Studies), 2023)
Incomplete medical record documentation affects the quality of service in hospitals. The migration of SIMRS is intended to allow hospital services to be integrated. The use of electronic medical records as a nursing care documentation tool needs to be evaluated in terms of the acceptance of technology through three constructs: the effect of benefits, the effect of ease of use of the system, and self-confidence in computing ability. The study aims to explore the nurses’ experiences of the influence of the benefits of using technology, the ease of use of technology, and nurses' self-confidence when using technology. This study used qualitative methodology with an exploratory phenomenological approach. Data were collected through FGDs with 12 participants selected by purposive sampling technique and consultation with information technology and nursing management experts. Data analysis used the Collaizi Model. The results obtained from this study indicate that the electronic care documentation system must consider the security system of the medical record and that obstacles to operating the system must be anticipated. Guidelines should be made for the application of 3S nursing care in EMR. Adapting to technology influences self-confidence in computing ability, the belief that technology can complete tasks, the usefulness of technology, and the ease of use of electronic documentation technology. It can be concluded that the evaluation of technology acceptance as early as possible is very important to support the successful use of information systems and provide input for management and policymakers in understanding the process of adaptation to new technologies and the creation of practical guidelines for the successful implementation of information systems.